Wholesome Dwellings - Graham, Malcolm (Archaeopress, 2020)
This study by Malcolm Graham, a leading Oxford local historian for many years, provides a fascinating insight into post-war housing needs in Oxford, and how the modern city evolved away from the university buildings and college quadrangles for which the city is internationally renowned
Description based on publisher supplied metadata and other sources
Keywords: Public housing-England-Oxford-History-20th century..; Oxford (England)-Social conditions-20th century